Aprendizagem solidária : inovação educativa no contexto dos projetos integradores em um curso superior de gastronomia - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present work deals with the application of solidary learning as an educational innovation in integrative projects, focused on social issues, in a Community Institution of Higher Education, with academics from the Higher Course of Technology in Gastronomy. In this research proposal, we start from the challenges that are launched by the community in the integrative projects platform of the institution locus of this research through the SOU I Platform. The SOU I Integrating Projects Platform is a site that unites students, communities and companies, created in 2019 with the objective of concentrating challenges registered by the community for the practice of extension and providing the academic with greater proximity to the community and the job market since the first semester of the course, through partnerships. The objective of this work is to show that solidary learning, as an educational innovation, is present in integrative projects aimed at solving social problems in the Higher Course of Technology in Gastronomy. As a research question, we seek to answer: How is solidary learning shown in integrative projects in the URCAMP Higher Education Course in Gastronomy Technology? The theoretical framework is built from the concepts of educational innovation proposed by Jaume Carbonell and the concepts of solidary learning, mainly following the authors Katia Mori and Maria Nieves Tapia. In addition, concepts and experiences related to solidary learning as an educational innovation in South America, Europe and the United States will be presented. As for the methodological procedures, the qualitative research approach will be used and as for the method, ethnographic research will be chosen. For the data analysis process, it is intended to use the content analysis technique, which according to Bardin (2011) presents objectivity, systematization and inference as methodological characteristics. For data collection, it is intended to use, in addition to the information contained in the integrated projects platform, participant observation, field notes and the focus group, among others. The research was based on social projects registered by the community on the SOU I integrated project platform and developed by academics of the Gastronomy course in 2020. The findings from the analysis revealed the field of convergences of solidary learning and educational innovation, in evidence of collaborative, challenging, critical and active learning, in addition to the role of students in the social project developed in the Superior Course of Technology in Gastronomy. It was concluded that integrative projects transform university practices and promote a space for integration that is conducive to the exercise of solidarity and autonomy to transform reality.
Keywords: Inovação educativa; Aprendizagem solidária; Projetos integrados; Educational innovation; Solidary learning; Integrated projects; CNPQ::CIENCIAS SOCIAIS APLICADAS